2019
DOI: 10.4236/jwarp.2019.1111080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cleaning Time in Household Reservoirs on Trihalomethane Formation in Treated Water

Abstract: Chlorination is an efficient and low-cost technique in disinfecting water for public water supply. However, during the process, the formation of undesirable by-products called halogen compounds, such as trihalomethanes (THMs), occurs. Some of these compounds are proven to be carcinogenic to laboratory animals. The goal of this study was to investigate the occurrence of THMs in household reservoirs and the influence of cleaning time of these reservoirs on the formation of THMs. A total of 103 households were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These findings are comparable with a related meta-analysis performed by Morris et al [ 49 ], which showed that chlorinated surface water has significantly more chlorination by products than chlorinated groundwater (medians of 50.7 and 0.8 ppb, respectively). Therefore, the consumption of surface water was found to be an indirect proxy of exposure to disinfection by products used in associated studies [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are comparable with a related meta-analysis performed by Morris et al [ 49 ], which showed that chlorinated surface water has significantly more chlorination by products than chlorinated groundwater (medians of 50.7 and 0.8 ppb, respectively). Therefore, the consumption of surface water was found to be an indirect proxy of exposure to disinfection by products used in associated studies [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%